PENGEMBANGAN DESAIN MEKANISME ZIG-ZAG PADA ALAT ORBITAL PIPE WELDING - Abdul Hafiz Fahrurrozi; Eko Prasetyo (Integrative Perspectives of Social and Science Journal, 2025)
Welding is a method of joining metals by melting the parent metal and filler metal with or without pressure and with or without the addition of metal and producing a continuous connection. In plate and pipe welding, many still use straight welding mechanisms, both vertical and horizontal, while the zigzag welding mechanism is still not widely used. Therefore, a welding mechanism was developed on pipes to support industry 4.0, namely Orbital pipe welding using a zigzag mechanism. Orbital pipe welding (OPW) is a tool created by humans to facilitate human work when wanting to connect two or more pipes into a series, where the welding tool is rotated 180° to 360°. The design process of Orbital pipe welding uses the VDI (Verein Deutcher Ingenieure) design method or called the VDI 2222 method, which is a systematic approach to design to formulate and direct various design methods that are increasingly developing due to research activities. The results of the research obtained during stress, strain, displacement and safety factor testing can be concluded from the analysis that it is declared safe.